Advanced procedure for estimation of pipeline embedment on soft clay seabed - Yu, S.Y. (Techno Press, 2017)
In the present study, the advanced procedure has been proposed to estimate higher accuracy of embedment of pipes that are installed on soft clay seabed. Numerical simulation by OrcaFlex simulation code was performed to investigate dynamics eabed embedment, and two steps, i.e., static and dynamic analysis, were adopted. In total, four empirical curves were developed to estimate the seabed embedment including dynamic phenomena, i.e., behaviour of vessel, environmental condition, and behaviour of nonlinear soil. The obtained results were compared with existing methods (named general method) such as design code or guideline to examine the difference of seabed embedment for existing and advance methods. Once this process was carried out for each case, a diagram for estimating seabed embedment was established. The applicability of the proposed method was verified through applied examples with field survey data. This method will be very useful in predicting seabed embedment on soft clay, and the structural behaviours of installed subsea pipelines can be changed by the obtained seabed embedment in association with on-bottom stability, free span, and many others. Copyright © 2017 Techno-Press, Ltd.